1998
DOI: 10.1080/09640569811704
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Waste and Electricity Demand in The Netherlands: A Hypothetical Intervention

Abstract: An important question in the present reorganization and liberalization of infrastructure networks in many countries is what kind of regulatory regimes can provide incentives for demand management and reduction in a future situation. In this paper, the present situation in the Dutch waste and electricity sectors is analysed. It is concluded that a quantity-based tariff system and the entwined interests of organizations are key impediments to effective demand management in these two sectors. A hypothetical inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Slingerland and Jong (1998) focused on the kind of regulatory body that will provide incentives for demand management and reduction in electricity consumption. The study concluded that a quantity-based tariff system and the entwined interests of organisations are the key impediments for an effective demand management in the electricity sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Slingerland and Jong (1998) focused on the kind of regulatory body that will provide incentives for demand management and reduction in electricity consumption. The study concluded that a quantity-based tariff system and the entwined interests of organisations are the key impediments for an effective demand management in the electricity sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another charging system for household waste would have a greater chance of bringing about change (Slingerland & de Jong 1998). The collection rates for industrial waste in Denmark and the Netherlands are established in competition between collectors.…”
Section: Comparison Of Core Elementsmentioning
confidence: 99%